Penerapan Digital Marketing untuk Peningkatan Pemasaran UKM Heppi Kitchen Depok - Putra Tangguh Wisnuaji; Dwi Rachmawati; Suci Ayu Sudari (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This activity aims to provide MSMEs to learn how create strategy marketing using food service delivery and to rising sales through development of digital marketing. Methodology: This activity assists with applying MSMEs through marketplace, help to promote product with copywriting, manage sales, create a digital catalogue, and develop, give instruction how to create design for packaging product. Results: This    dedication    output upgrade knowledge of product, registering MSME address to food services delivery accounts, understanding how to expanding market and sales reach using digital marketing, Social Media and food service delivery. Conclusions: The activities carried out by the Abdimas Team so that Heppi Kitchen Depok MSMEs become more competitive MSMEs include Development of Social Media Marketin and Development of digital marketing Limitations: Limitation of this study is on totat number MSMEs. Contribution: These MSMEs have helped gaining more income of selling the products. One strategy that can be used to survive this challenge is to maximize online sales.